Conformational differentiation of α‐cyanohydroxycinnamic acid isomers: a Raman spectroscopic study. (27th July 2017) - Vedad, Jayson; Domaradzki, Maciej E.; Mojica, Elmer‐Rico E.; Chang, Emmanuel J.; Profit, Adam A.; Desamero, Ruel Z. B.
Abstract : Two α‐cyanohydroxycinnamic acid positional isomers, α‐cyano‐4‐hydroxycinnamic acid (CHCA4) and α‐cyano‐3‐hydroxycinnamic acid (CHCA3), were characterized by using Raman spectroscopy. We analysed the implications of the collected Raman spectral shifts, and verified them through other spectroscopic techniques, to arrive at plausible three dimensional structures of CHCA3 and CHCA4. The positions of these groups were mapped by systematically analysing the orientation and type of interactions functional groups make in each CHCA isomer. We determined whether or not the carboxylic moieties are forming dimeric links and ascertained the existence of ring–ring π‐stacking interactions. We also assessed the nature of the hydrogen bonding between –CN and –OH groups. The results were then taken together to model plausible three‐dimensional structures for each compound. The data revealed a structure for CHCA4 that matches the published X‐ray crystallographic structure. We then applied the same spectral analysis to CHCA3 to reveal its plausible three‐dimensional structure. The structural details revealed may account for the functional properties of the two α‐cyanohydroxycinnamic acid positional isomers. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : Two positional isomers of α‐cyanohydroxycinnamic acid with different properties were characterized by using Raman spectroscopy. By analysing and comparing their different spectral shifts, we were able to construct the three‐dimensional structure of both isomers which can help explain their different physico‐chemical properties.